Efficacy and Safety Profile of Montgomery T-Tube Implantation in Patients with Tracheal Stenosis - Feng-Jie Wu; Yang-Wei Yao; En-Guo Chen; Hui-Hui Hu; Jian-Ping Jiang; Meng Yang; Yang-Yang Gu; Da-Kui Cao; Ye-Li Zhu (Canadian Respiratory Journal)
Background. Tracheal stenosis is able to lead to airway obstruction. Objective. To evaluate the efficacy and safety profile of Montgomery T-tube implantation in patients with tracheal stenosis. Methods. Fifty-two patients with tracheal stenosis diagnosed between 2016 and 2019 were included in this retrospective cohort study. The patients were divided into observation group (n = 25 cases) and control group (n = 27). The therapeutic effect, arterial blood gas analysis, arterial oxygen partial pressure (PaO2), arterial carbon dioxide partial pressure (PaCO2), shortness of breath score, airway diameter change, dyspnea score, quality of life, and safety were compared between the two groups before and after treatment. Results. The therapeutic effect of the observation group gained better results than that of the control group (84.00% vs. 62.96%). One week after operation, the pH value, SaO2, PaCO2, shortness of breath score, airway diameter change, dyspnea score, life quality, and incidence of postoperative complications in the observation group exerted better results as compared to the control group. Conclusion. The implantation of Montgomery T-tube has effective function in terms of improving the symptoms of dyspnea and the life quality of patients with safety profile in patients harboring tracheal stenosis.